Effects of sugar sources on adult longevity, survival and related gene expression in an endoparasitoid, Pteromalus puparum (Hymenoptera: Pteromalidae). Issue 3 (31st October 2020) - Xiong, Shijiao; Yu, Kaili; Yao, Hongwei; Wang, Fang; Fang, Qi; Song, Qisheng; Ye, Gongyin
Abstract: BACKGROUND: Adult parasitic wasps take sugars to meet their energy needs and display different lifespans and fertility in response to different sugar sources. Pteromalus puparum is an endoparasitoid with a wide range of hosts, including many lepidopteran pests. As a potential natural enemy resource, the availability of sugar sources has profound effects for wasp applications and host populations dynamics. RESULTS: We assessed the effect of feeding sucrose and honey on the lifespan of P. puparum in the range 0–40% ( w/v ). The results indicated a statistically significant positive effect of sucrose and honey solutions on the lifespan of P. puparum female adults. Correlation analyses confirmed a strong positive correlation between high concentrations of sugar and extended lifespan. The optimum concentration of sucrose solution for wasps was 20%, while 10% for honey. Then, we examined the expression patterns of 15 lifespan‐related genes. The results showed that the relative expression levels of 14 genes were significantly correlated with the mean lifespan of sucrose‐fed wasps, and six genes correlated with the mean lifespan of honey‐fed wasps. In addition, the models for lifespan prediction were constructed. CONCLUSION: We elaborated the quantitative effects of two sugar sources (sucrose and honey) on P. puparum lifespan, investigated the expression patterns of lifespan‐related genes when fed different sugar sources, and developed round lifespan prediction models accordingly. This study provides a novel tool for studying the longevity regulating mechanisms of parasitic wasps, and may be instructive for mass‐production of parasitoids as biological control agents. © 2020 Society of Chemical Industry Abstract : Lifespan prediction models for P. puparum taking sugar sources. The lifespan of Pteromalus puparum increased with the concentrations of sucrose and honey solution. The optimum concentrations of sucrose and honey were 20% and 10%, respectively. Many lifespan‐related genes changed depending on sugar concentrations. Reliable lifespan prediction models were established accordingly. PpPTEN, PpSOD1‐1 and PpSOD1‐3 were included as independent variables in the lifespan prediction model for sucrose, while PpTSC2‐2, PpHDAC1 and PpTSC2‐3 were included in the model for honey.